Magazine alcohol advertising compliance with the Australian Alcoholic Beverages Advertising Code - Donovan, K.; Donovan, Robert; Howat, Peter; Weller, Narelle (Informa Healthcare, 2007)
The purpose of this study was to assess the frequency and content of alcoholic beverage advertisements and sales promotions in magazines popular with adolescents and young people in Australia, and assess the extent to which the ads complied with Australia's self-regulatory Alcoholic Beverages Advertising Code (ABAC). Alcohol advertisements and promotions were identified in a sample of 93 magazines popular with young people. The identified items were coded against 28 measures constructed to assess the content of the items against the five sections of the ABAC. Two thirds of the magazines contained at least one alcohol advertisement or promotion with a total of 142 unique items identified: 80 were brand advertisements and 62 were other types of promotional items (i.e. sales promotions, event sponsorships, cross promotions with other marketers and advertorials).It was found that 52% of items appeared to contravene at least one section of the ABAC. The two major apparent breaches related to section B-the items having a strong appeal to adolescents (34%) and to section C-promoting positive social, sexual and psychological expectancies of consumption (28%). It was also found that promotional items appeared to breach the ABAC as often as did advertisements. It is concluded that the self-regulating system appears not to be working for the alcoholic beverages industry in Australia and that increased government surveillance and regulation should be considered, giving particular emphasis to the inclusion of promotional items other than brand advertising.